An inkjet-printed microstrip patch sensor for liquid identification - Hassan, Arshad; Lee, KiBae; Bae, Jinho; Lee, Chong Hyun (Sensors and actuators. A. Physical., 2017)
•A novel RF microstrip patch sensor for liquid identification is proposed .•The resonance frequencies of sensor depend on sensor geometry and dielectric constants of liquids.•Design procedure is used to find maximum resonance separation and minimum reflection coefficient.•Low-cost and fast inkjet printing is used for sensor patch fabrication. In this paper, we propose a compact microstrip patch sensor using radio frequency (RF) signals to identify different liquids. The operation of the proposed sensor depends on the fact that liquids of different dielectric constants have different resonance frequencies. The proposed patch sensor is composed of radiator and ground fabricated by silver nanoparticle (AgNPs) ink and separated by empty chamber of 5mm height for containing liquid sample. The radiator and the ground are printed on glass substrate by using commercialized inkjet printer Dimatix Material Printer (DMP). To obtain the best sensor parameters, we propose simple design procedure, which finds not only maximum frequency separation between two adjacent resonance frequencies but also lowest reflection coefficients at the resonance frequencies. Through finite element method based ANSYS high frequency structure simulator (HFSS) simulation, we obtain sensor parameters, which can identify water, ethanol, water/ethanol 50:50 and synthetic engine oil. The designed sensor has at least 80MHz resonance frequency separation and shows maximum −25dB reflection coefficients at resonant frequencies. Remarkably, the fabricated sensor has 140MHz minimum frequency separation and maximum −29dB reflection coefficient. By comparing existing sensors, we show that the proposed sensor has outstanding identification capability. Therefore, the proposed patch sensor can be utilized in RF tunable liquid detection applications.